Expansionary fiscal contraction : the Thatcher government's 1981 budget in perspective - Needham, Duncan; Hotson, Anthony (Cambridge : Cambridge University Press, 2014)
In its 1981 Budget, the Thatcher government discarded Keynesian counter-cyclical policies and cut Britain's public sector deficit in the depths of the worst UK recession since the 1930s. Controversially, the government argued that fiscal contraction would produce economic growth. In this specially commissioned volume, contributors examine recently released archives alongside firsthand accounts from key players within No. 10 Downing Street, HM Treasury and the Bank of England, to provide the first comprehensive treatment of this critical event in British economic history. They assess the empirical and theoretical basis for expansionary fiscal contraction, drawing clear parallels with contemporary debates on austerity in Europe, USA and Japan in the wake of the recent global financial crisis. This timely and thoughtful book will have broad appeal among economists, political scientists, historians and policy makers.
Foreword Geoffrey Howe -- 1. The 1981 statement by 364 economists / Robert Neild -- 2. The 1981 Budget: how did it come about? / Tim Lankester -- 3. The London Business School and the 1981 Budget / Alan Budd -- 4. The 1981 Budget: a view from the cockpit / Adam Ridley -- 5. The Bank of England and the 1981 Budget / Charles Goodhart -- 6. 1981 and all that / William Keegan -- 7. The origins of the Budget in 1980 / Christopher Collins -- 8. The 1981 Budget and its impact on the conduct of economic policy: was it a monetarist revolution? / Anthony Hotson -- 9. The 1981 Budget: 'a Dunkirk, not an Alamein' / Duncan Needham -- 10. Macro-economic policy and the 1981 Budget: changing the trend / Ray Barrell -- 11. The Keynesian twin deficits in an inflationary context / Robert Z. Aliber -- 12. The long road to 1981: British money supply targets from DCE to the MTFS / Michael Oliver -- List of names -- Chronology of events -- Official sources -- Bibliography of cited sources -- Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Thatcher, Margaret; Budget -- Great Britain -- History; Fiscal policy -- Great Britain -- History; Great Britain -- Economic policy -- 1979-1997.